Akad dalam Perspektif Filsafat Hukum Islam - Sofuan Jauhari (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2015)
In an era of globalization, typology of contract covenants must not only be done in one place but also penetrated the online channels (e-commerce). Islamic law as a legal umbrella to be able to accommodate any developments typology of existing contracts. Review of contracts in the perspective of the philosophy of Islamic law meant to discuss the fundamental issues about the nature of the contract in Islamic law to find and cherished values (wisdom) wisdom through contemplation, the formulation of values and harmonize the mind (logical), so the purpose of the contract will be achieved. The purpose of the contract is the subject of the contract when the purpose of transferring the contract.